MEMBANGUN KARAKTER SISWA MELALUI KEPEMIMPINAN INKLUSIF DI SEKOLAH DASAR - Fathul Jannah; Ahmad Suriansyah; Sulistiyana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This article discusses the role of inclusive leadership in shaping students' character in elementary schools. Through a literature review and analysis of recent research findings, it was found that inclusive leadership implemented by school principals can create a learning environment that is safe, values diversity, and encourages the development of character values such as tolerance, empathy, responsibility, and cooperation. The application of inclusive leadership has a positive impact on students' character development by creating an inclusive and participatory atmosphere in schools. However, the implementation of inclusive leadership faces challenges such as limited training for teachers and principals, as well as a lack of resources to support students with special needs. This article recommends strengthening the capacity of school principals in managing diversity and emphasizes the importance of synergy between teachers, students, and the school community.